STUDI LITERATUR: PERAN KOMPONEN EKOSISTEM SEKOLAH DALAM MENDUKUNG KESEJAHTERAAN - Siregar, Julinda; Akhiroh, Muhibatur Rohmatul; A’liyah, Umi Habibatul; Putri, Desti Nurdiana Eka; Sulistyorini, Kurniasari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
One of the key indicators to measure the success of the quality and process of education in schools is school well-being. The school environment plays an important role in influencing the well-being of its entire community, including students, teachers, staff, and other elements involved in the school ecosystem. This research is a literature study that aims to analyse the role of school ecosystem components in supporting the well-being of all elements in the school. The method used in this research is a systematic literature review of national and international journals in the last ten years that are relevant to the topic of school ecosystem and school well-being. The steps in this research are: 1) literature search process; 2) determining selection criteria; 3) literature analysis; 4) synthesising. The results showed that the school ecosystem components collectively and individually play an important role in shaping school well-being. These components include: 1) positive school climate; 2) curriculum and teaching that support well-being; 3) physical health and physical environment of the school that support well-being; 4) parental and community engagement; 5) teacher and staff well-being. In general, it can be concluded that creating a prosperous ecosystem requires a holistic and integrated approach. Where each component can interact harmoniously to support the optimal growth and development of all school members. ABSTRAKSalah satu indikator kunci untuk mengukur keberhasilan kualitas dan proses pendidikan di sekolah adalah kesejahteraan sekolah. Lingkungan sekolah memegang peranan penting dalam mempengaruhi kesejahteraan seluruh komunitasnya mulai dari siswa, guru, staf, dan unsur lain yang terlibat dalam ekosistem sekolah. Penelitian ini merupakan studi literatur yang bertujuan untuk menganalisis peran komponen ekosistem sekolah dalam mendukung kesejahteraan semua elemen di sekolah. Metode yang digunakan dalam penelitian ini adalah kajian literatur sistematis terhadap jurnal nasional dan internasional dalam sepuluh tahun terakhir yang relevan dengan topik ekosistem sekolah dan kesejahteraan sekolah. Langkah-langkah dalam penelitian ini yaitu: 1) proses pencarian literatur; 2) menentuan kriteria seleksi; 3) analisis literatur; 4) melakukan sintesis. Hasil penelitian menunjukkan komponen ekosistem sekolah secara kolektif dan individual memiliki peran penting dalam membentuk kesejahteraan sekolah. Komponen-konponen tersebut meliputi: 1) iklim sekolah yang positif; 2) kurikulum dan pengajaran yang mendukung kesejahteraan; 3) kesehatan fisik dan lingkungan fisik sekolah yang mendukung kesejahteraan; 4) keterlibatan orang tua dan komunitas; 5) kesejahteraan guru dan staf. Secara umum dapat disimpulkan bahwa menciptakan ekosistem yang Sejahtera memerlukan pendekatan yang holistic dan terintegrasi. Dimana setiap komponen dapat berinteraksi secara harmonis untuk mendukung pertumbuhan dan perkembangan secara optimal seluruh warga sekolah.